"Reconhecimento de Nêmesis": momentos do Grã Cão - Rabello, Ivone Daré (Revista do Instituto de Estudos Brasileiros, 1988)
In this article the poem "Reconhecimento de Nêmesis", in the book "A costela do Grã Cão" by Mário de Andrade, is interpreted through a stylistic and thematic anlisys. In the text the lyric "I" reveals an "other", an "intruder", to itself -- the boy from his childhood that invades him -- and depicts the world of ordinary men as antagonistic to him. From these themes -- i. e.: internal breakdown and desagreement with the world -- I investigate the way in which the text is constructed, in the unit form/meaning, emphasizing the tension that exist between two rhythms: that of the world which tends toward uniformization and that of poetry which resists uniformization. This tension results in the exposure of the breakdown of the poetic "I" and his impossibility to follow the pace of ordinary men. From this reading, the article finally points out some interpretative data for the books "A costela do Grã Cão" and "Livro azul" which are understood as complementary moments in Mário de Andrade's work; the first comes from one who preaches the kingdom of freedom through an exorcizing and revolutionary poetry.